Profound Autonomic Instability Complicated by Multiple Episodes of Cardiac Asystole and Refractory Bradycardia in a Patient with Anti-NMDA Encephalitis - Stephanie R. Mehr; Roy C. Neeley; Melissa Wiley; Avinash B. Kumar (Case Reports in Neurological Medicine)
Anti-N-methyl-D-aspartate receptor encephalitis (anti-NMDARE) is autoimmune encephalitis primarily affecting young adults and children. First described about a decade ago, it frequently manifests as a syndrome that includes progressive behavioral changes, psychosis, central hypoventilation, seizures, and autonomic instability. Although cardiac arrhythmias often accompany anti-NMDARE, the need for long-term electrophysiological support is rare. We describe the case of NMDARE whose ICU course was complicated by progressively worsening episodes of tachyarrhythmia-bradyarrhythmia and episodes of asystole from which she was successfully resuscitated. Her life-threatening episodes of autonomic instability were successfully controlled only after the placement of a permanent pacemaker during her ICU stay. She made a clinical recovery and was discharged to a skilled nursing facility after a protracted hospital course.